The applicability of nature-based interventions to support mothers’ postnatal wellbeing: A conceptual review - Katherine Hall; Christopher Barnes; Lucy Duggan; Samantha Walton; Paul Moran; Katrina Turner; Jonathan Evans (Wellbeing, Space and Society, 2024)
Nature-based interventions represent promising candidates for supporting mothers and infants in the postnatal period, which is a vulnerable time for mothers to experience mental health difficulties. Possible mechanisms by which nature-based interventions may support postnatal health include those of a biological/physiological nature (for example natural light optimising circadian rhythm, improving microbiome health, providing opportunities for physical activity), relational/social pathways, and cognitive and creative pathways. A conceptual understanding of these possible mechanisms will aid the design and evaluation of postnatal nature-based interventions.